Effect of Aluminum Oxide Nanoparticles Fuel Additives on the Performance and Emissions of Diesel Engine - H.A. Dhahad; A.S. Hamadi; S.A. Ali (Engineering and Technology Journal, 2017)
The effect of Aluminum Oxide (AL2O3) nanoparticles fuel additives on the performance and emission characteristics of diesel engine was investigates. Diesel fuel was mixed with the (AL2O3) nanoparticles in the mass fractions of 100 and 150 ppm by using ultrasonicator. Direct injection (DI), by using fiat diesel engine that run at fixed speed (1500 rpm) and constant fuel injection pressure (400 bar) with varying the operation load. The gain result was likening with those obtain when the operation the diesel engine with normal fuel. Measurements indicated that there is enhancement in the thermal efficiency and the brake specific fuel consumption with increasing the dosing level of (AL2O3) nanoparticles in the blended fuel. The emission results at all loads showed that NOx and smoke produced by (AL2O3) blended fuels were less than those produced by diesel fuel. Diesel fuel produced CO and HC more than (AL2O3) blended fuels at high load and less at low load.